Ação de proteínas isoladas de plantas na hemostasia e trombose - Salu, Bruno Ramos [UNIFESP] (2017)
Protein from plants may act as inhibitors and thus used to assess blood coagulation, thrombosis and inflammation, in order. to determine the role of certain coagulation enzymes in hemostasis. Such inhibitors may be considered for the development of novel antithrombotic drugs. The isolated inhibitors from Enterolobium contortisiliquum (EcTI), Oelonix regia (DrTI), Acacia schweinfurthii (ASTI), and the bifunctional CrataBL protein, a lectin with inhibitory activityextracted from the Crataeva tapia bark, distinctly inhibit proteases, among them, the coagulation enzymes. Our objective was to establish the structure and function relationship of the inhibitors and their effects on thrombus formation. The inhibitors were purified by ion-exchange, molecular exclusion and affinity chromatoqraphies. The homogeneity of the preparations was assessed by SDS-PAGE, reverse phase chromatography and mass spectrometry, depending on the inhibitor. The effect on coagulation was assessed by the partially activated thromboplastin time, TTPa, and thrombin time, TP. The effects on platelet aggregation were investigated in vitro and ex vivo, as well as in the models of arterial thrombosis via injection of rose bengal in mice, and venous thrombosis through vena cava ligation in rats for the estimation of thrombus formation in vivo. DrTI, AsTI and EcTI increased the aPTT in human plasma due to the inhibition of huPK. DrTI differs from AsTI and EcTI by inhibiting FXla, with a Kiapp of 1.3 nM, indicating the dynamic nature of their reactive sites. DrTI, AsTI, EcTI and CrataBL significantly prolonged the time for total carotid artery occiusion in mice compared to the NaCI control. EcTI was also effective in decreasing the venous thrombus (74%, 2 mg/kg). The effects of DrTI, AsTI and EcTI can be attributed to their activities on the contact blood coagulation enzymes and, in the case of DrTI, AsTI and CrataBL, with platelet inhibition, since these proteins inhibited ex-vivo mice platelet aggregation induced by ADP. Although CrataBL has slight inhibitory effect on FXa it has a potent neutralizing effect of heparin activity. In conclusion, the compounds showed antithrombotic action in experimental models of arterial and venous thrombosis, ali interfering in the intrinsic,' but not in the extrinsic coagulation pathway. Only CrataBL was capable of interacting and neutralizing the effect of heparin. As none of the proteins altered the time of bleeding, it is plausible to consider them for therapeutic application, inhibiting thrombus development with a lower hemorrhagic effect. Support by FAPESP, CNPq, CAPES, Ethics Committee N° 179311